First-principles quantum dynamical theory for the dissociative chemisorption of H2O on rigid Cu(111) - Zhaojun Zhang (Nature Portfolio, 2016)
Dissociative chemisorption dynamics of polyatomic molecules on surfaces are still challenging to probe quantitatively. Here, the authors report the 9-dimensional quantum dynamics of H2O dissociative chemisorption on Cu(111), with the highest level of accuracy yet seen for this prototypical reaction.